Systematic Physical Exercise and Spirulina maxima Supplementation Improve Body Composition, Cardiorespiratory Fitness, and Blood Lipid Profile: Correlations of a Randomized Double-Blind Controlled Trial - Marco Antonio Hernández-Lepe; Francisco Javier Olivas-Aguirre; Luis Mario Gómez-Miranda; Rosa Patricia Hernández-Torres; José de Jesús Manríquez-Torres; Arnulfo Ramos-Jiménez (MDPI AG, 2019)
Cardiovascular diseases are part of the highly preventable chronic diseases associated with changes in lifestyle. Within them, physical activity, low-fat and high-fiber diets are distinguished as the main support for prevention, even when supplementation with nutraceuticals has become a very common practice. Fifty-two young sedentary men with excess body weight (body mass index (BMI) ≥ 25 kg·m−2) were enrolled in a randomized-crossover controlled trial [six weeks of a systematic physical exercise with Spirulina maxima or placebo supplementation (4.5 g·day−1)]. Body composition, blood lipid profile, and maximal oxygen uptake were determined pre/post intervention. Pairwise comparisons showed a significant improvement (p < 0.01) on blood lipid profile in the group of exercise plus Spirulina maxima. Moreover, correlations of absolute changes of BMI, body fat percentage, blood lipids and maximal oxygen uptake were statistically significant (p < 0.01). These results indicate that the Spirulina maxima supplementation could be acting in a synergistic way with exercise due to the enhanced effects on body composition, cardiorespiratory fitness, and blood lipid profile. This phenomenon should be considered to reduce risk of cardiovascular disorders. Trial registration: Clinical Trials, NCT02837666 (July 19, 2016).